Comorbid autoimmune diseases and burden of diabetes-related complications in patients with type 1 diabetes from a Mediterranean area. (September 2022) - Gimenez-Perez, Gabriel; Vlacho, Bogdan; Navas, Elena; Mata-Cases, Manel; Real, Jordi; Cos, Xavier; Franch-Nadal, Josep; Mauricio, Didac
Highlights: Type 1 diabetes is frequently associated with other autoimmune diseases, the most frequent being autoimmune hypothyroidism. Patients with type 1 diabetes and other autoimmune diseases are more often female.- Patients with type 1 diabetes and other autoinmune disesases are older and their age of onset of diabetes is higher. - Autoimmune thyroid diseases are associated with a lower prevalence of kidney disease and peripheral artery disease. - In contrast, the presence of other autoimmune diseases is associated with a higher prevalence of ischemic heart disease. Abstract: Aim: To assess the prevalence of autoimmune diseases (AID) in patients with type 1 diabetes (T1D) and to evaluate whether the rate of diabetes-related complications differs depending on the presence of AID. Methods: Cross-sectional analysis of 13, 570 T1D patients aged ≥ 18 years registered in the SIDIAP database. The association between AID and diabetes-related complications was assessed by multivariable logistic regression models. Results: The prevalence of AID was 18.3% with thyroid AID being the most common. Patients with T1D and AID were more often female and their current age, age of diabetes onset and diabetes duration were higher. Patients with only thyroid AID experienced a lower risk of peripheral artery disease (odds ratio [OR] = 0.51, 95%; confidence interval [CI] 0.31 to 0.81) and kidney disease (OR = 0.68, 95%; 95% CI 0.54 to 0.85), whereas patients with other AID had an increased risk of ischemic heart disease (OR = 1.48, 95%; 95% CI 1.04 to 2.06). Conclusions: The burden of diabetes-related complications in patients with T1D differs according to the type of additional AID. The presence of diabetes complications is lower in those with autoimmune thyroid disease while the presence of other AID is associated with higher rates of ischemic heart disease.